2001
DOI: 10.1097/00005392-200107000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Extraperitoneal Laparoscopic Pyeloplasty: A Multicenter Study of 55 Procedures

Abstract: Retroperitoneal laparoscopic pyeloplasty seems to be a valuable alternative to open pyeloplasty for ureteropelvic junction obstruction. The long-term outcome must be assessed before this procedure may be definitively validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 22 publications
2
29
2
Order By: Relevance
“…Our intra-and postoperative complications (5%) were comparable to the other published series, which have reported postoperative complication rates of 2-13% [12][13][14][15]. Furthermore, our mean operative time of about 2 h without conversion can be compared with other published series of laparoscopic pyeloplasty, in which the mean operative time was 140 min (range: 37-368) [16][17][18].…”
Section: Discussionsupporting
confidence: 83%
“…Our intra-and postoperative complications (5%) were comparable to the other published series, which have reported postoperative complication rates of 2-13% [12][13][14][15]. Furthermore, our mean operative time of about 2 h without conversion can be compared with other published series of laparoscopic pyeloplasty, in which the mean operative time was 140 min (range: 37-368) [16][17][18].…”
Section: Discussionsupporting
confidence: 83%
“…Laparoscopic transperitoneal and retroperitoneal series have reported success rates of 93% to 100% [38][39][40][41][42][43][44]. Bauer et al [45] noted essentially equivalent rates of post- A retroperitoneoscopic approach for pyeloplasty provides more direct access to the renal pelvis but provides a more restrictive working space for laparoscopic suturing.…”
Section: Laparoscopic Pyeloplastymentioning
confidence: 99%
“…Bauer et al [45] noted essentially equivalent rates of post- A retroperitoneoscopic approach for pyeloplasty provides more direct access to the renal pelvis but provides a more restrictive working space for laparoscopic suturing. Soulie et al [43] reported a multi-institutional series of 55 patients undergoing retroperitoneoscopic pyeloplasty during which crossing vessels were transposed in 20 of 23 (87%) cases. Mean operative time for the procedures was 185 minutes, and the overall success rate was 96%.…”
Section: Laparoscopic Pyeloplastymentioning
confidence: 99%
“…For example, in the case of radical nephrectomy, Rassweiler et al [40] found that the transperitoneal approach was, on average, 5 minutes shorter than the extraperitoneal approach. However, the [48] 100 320 Janetschek et al [49] 73 142 Hernandez et al [50] 56 158 Gill et al [51] 100 168 Cicco et al [52] 50 139 Rassweiler et al [40] 18 206 17 211 Adrenalectomy Fernandez-Cruz et al [17] 10 89 11 105 Naya et al [53] 28 202 22 221 Guazzoni et al [54] 145 160 Salomon et al [46] 115 118 Pyeloplasty Turk et al [55] 49 165 Jarrett et al [56] 100 250 Soulie et al [57] 55 185 difference in average operative time with the same procedure in two different centers can be as high as 178 minutes. In other words, operative time seems to depend more on the standardization of the procedure and surgical experience than on the operative approach.…”
Section: Anatomical Considerations: Ergonomymentioning
confidence: 99%